2018
DOI: 10.1123/jsm.2017-0263
|View full text |Cite
|
Sign up to set email alerts
|

The Reverse Socialization of Sport Fans: How Children Impact Their Parents’ Sport Fandom

Abstract: While the sport fan literature suggests that it is common for parents to socialize their children to cheer for specific sports and teams, recent literature proposes that children can socialize their parents into changing the parents’ sport fandom in a process sociologists and consumer behavior researchers refer to as reverse socialization. To ascertain whether children can socialize and influence their parents’ sport fandom, 20 sport fan parents were interviewed. Evidence of reverse socialization was found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 32 publications
2
30
2
4
Order By: Relevance
“…School programs was the second of five team-initiated factors that led to fan socialization. Although some participants may not have been school age when becoming a fan, Mastromartino, Zhang and Wann [20] noted that sometimes parents would become socialized through the school programs of their child, supporting findings from Hyatt, Kerwin, Hoeber and Sveinson [23]. Participants felt that they or their child found school programs to be beneficial and provided value to them, contributing to their socialization as a fan of the team, specifically leading to an increased sense of civic pride.…”
Section: Team-initiated Socialization Agentsmentioning
confidence: 78%
See 2 more Smart Citations
“…School programs was the second of five team-initiated factors that led to fan socialization. Although some participants may not have been school age when becoming a fan, Mastromartino, Zhang and Wann [20] noted that sometimes parents would become socialized through the school programs of their child, supporting findings from Hyatt, Kerwin, Hoeber and Sveinson [23]. Participants felt that they or their child found school programs to be beneficial and provided value to them, contributing to their socialization as a fan of the team, specifically leading to an increased sense of civic pride.…”
Section: Team-initiated Socialization Agentsmentioning
confidence: 78%
“…Previous research has concluded that the main influences on one's socialization process includes the fan's family, peers, schoolmates, coaches, local community, media, team/league promotions, and playing experience [16][17][18][19]22]. Additionally, Hyatt, et al [23] found that sometimes, it can be a child who socializes a parent into fandom. These results have held up over the years, yet with a changing sport consumption landscape and a focus on niche markets, these results may not be applicable.…”
Section: Socialization Theory and Identity Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Children may lead women to consume more sport for social or relationship building reasons (Farrell et al, 2011;Gantz and Wenner, 1991) and they sometimes nurture parents' fan identities (Hyatt et al, 2018). Therefore, we posit: Hypothesis #2: Number of resident children will be positively associated with women's sport consumption.…”
Section: Family Structurementioning
confidence: 96%
“…In fact, nurturing and investing in family-based interactions and cultures around sport is often perceived as "good" parenting (Eckstein, 2017;Knoester & Fields, 2020;Knoester & Randolph, 2019;Wheeler, 2011). Yet, parents may also become immersed in sport interactions and come to embrace the perceived benefits of sport from their children's own interests and activities (Dorsch et al, 2009(Dorsch et al, , 2015Hyatt et al, 2018;Knoester & Fields, 2020;Knoester & Randolph, 2019). Consequently, having parents who are more passionate about sports and having children of one's own may encourage individuals to possess greater belief in the personal development and social capital benefits of sport.…”
Section: Primary Group Influencesmentioning
confidence: 99%